THE EFFECT OF WORK STRESS AND WORKPLACE CONFLICT ON JOB PERFORMANCE AT PT. TIRTA INVESTAMA, AIRMADIDI - Massie, Patricia Magda Yull (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Many companies are trying to avoid the workplace stress, since it could effects the performance of employee. That’s why negative effects of work stress and workplace conflict also become a concern of HR manager. Since those things can bring so many problem like cardiovascular problem, depression and increase the possibility to catch another disease. Work Stress is the adverse reaction people have to exercise pressures and Workplace Conflict contains a variety of personalities that can something clash, creating a high potential for conflict. The objectives of this researchare to analyze the influence of work stress and work-place conflict on job performancesimultaneously and partially.The population in this research is all the employee of PT.Tirta Investama, Airmadidi.The sample of this research is 100 respondents or employees at PT.Tirta Investama, Airmadidi. This research’s findings are concluded as follows:Work Stress and Work-place Conflict influenceJob Performance at PT. Tirta Investama, Airmadidi simultaneously. Work Stress influence Job Performance at PT. Tirta Investama, Airmadidi partially andWork-place Conflict influence Job Performance at PT. Tirta Investama, Airmadidi partially. This research shows that work stress has the most significant influence to employees performance, than theyshould concern more on reducing work stress. Keywords: work stress, workplace conflict, job performance